2014
DOI: 10.3109/08916934.2014.906582
|View full text |Cite
|
Sign up to set email alerts
|

TH17 cells are increased in the peripheral blood of patients with SAPHO syndrome

Abstract: To assess whether the immune derangement previously observed in SAPHO syndrome could be linked to variations in blood TH1, TH2 or TH17 lymphocytes frequency. Seven SAPHO patients with a protracted course of the disease were studied ex-vivo for intracellular cytokines production by means of flow-cytometry and compared with matched groups of Psoriatic Arthritis patients and healthy controls. The Kruskal-Wallis test on the median of the three categories showed that there is a significant association between the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 31 publications
0
48
0
1
Order By: Relevance
“…In addition, an upregulation of IL‐8, IL‐17, IL‐18, TNF‐α and IL‐1 have been shown . We did not find evidence of elevated serum cytokines (IL‐1β, IL‐6, IL‐8, IL‐12, interferon‐γ, TNF‐α and soluble IL‐2 receptor α) in our patient, but these investigations were done during treatment and no baseline levels were performed.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, an upregulation of IL‐8, IL‐17, IL‐18, TNF‐α and IL‐1 have been shown . We did not find evidence of elevated serum cytokines (IL‐1β, IL‐6, IL‐8, IL‐12, interferon‐γ, TNF‐α and soluble IL‐2 receptor α) in our patient, but these investigations were done during treatment and no baseline levels were performed.…”
Section: Discussionmentioning
confidence: 51%
“…IL‐17 is a cytokine produced by Th17 cells, which have been shown to be increased in patients with SAPHO syndrome . As secukinumab had to be discontinued in our patient because of a hypersensitivity reaction with a positive lymphocyte transformation test, we introduced a treatment with apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence points to P2X7R as a main player in Th17 differentiation and IL‐17 secretion . In line with these findings, Th17 cells were recently found to be increased in the peripheral blood of patients with SAPHO …”
Section: Synovitis Acne Pustulosis Hyperostosis and Osteitismentioning
confidence: 55%
“…62 In line with these findings, Th17 cells were recently found to be increased in the peripheral blood of patients with SAPHO. 63 The hereditary basis of SAPHO has been supported by the finding of familial clustering cases, 64 but no specific mutations have been found in patients with SAPHO. PSTPIP2, which is involved in macrophage activation, neutrophil motility and osteoclast differentiation, has recently been supposed to play a role in innate immunity and development of autoinflammatory bone disorders, including SAPHO syndrome.…”
Section: Synovitis Acne Pustulosis Hyperostosis and Osteitismentioning
confidence: 99%
“…Another study demonstrated that by altering the composition of the intestinal microbiome with dietary manipulations, it was possible to modify the expression of sterile osteomyelitis phenotype [15]. Furthermore, recent human immunologic studies have identified increased Th17 cells in the peripheral blood of SAPHO patients [16], reduced IL-10 production by stimulated monocytes from CRMO patients [17], and increased expression of the inflammasome-related genes, IL1B , CAS1 , and ASC , in PBMC from CRMO patients [18]. …”
Section: Chronic Recurrent Multifocal Osteomyelitis and Autoinflammatmentioning
confidence: 99%